Public versus private information systems: do they differ in important ways? A review and empirical test - Rocheleau, Bruce; Wu, Liangfu (2002)
Bozeman and Bretschneider's (1986) seminal work posited that there are important differences between public and private information systems and that different principles should be used in the management of these systems. However, little empirical research has been conducted concerning this topic. The authors developed hypotheses based on the argument that competition forces businesses to use information technology (IT) as a weapon to gain competitive advantage that makes it more likely they will view IT as more important and be willing to invest more resources in IT. They test these hypotheses by comparing samples of municipalities and private organizations. The results confirmed that private sector organiz ations, despite the low amounts they invest in training, rate IT as important as does the private sector. - Reproduced.
Keywords: Information systems